Sodium‐glucose co‐transporter‐2 inhibitors and the risk of urosepsis: A multi‐site, prevalent new‐user cohort study. Issue 9 (4th June 2020) - Fisher, Anat; Fralick, Michael; Filion, Kristian B.; Dell'Aniello, Sophie; Douros, Antonios; Tremblay, Éric; Shah, Baiju R.; Ronksley, Paul E.; Alessi‐Severini, Silvia; Hu, Nianping; Bugden, Shawn C.; Ernst, Pierre; et al.
Abstract: Aim: To compare urosepsis rates in patients with type 2 diabetes treated using sodium‐glucose co‐transporter‐2 inhibitors (SGLT2i) with dipeptidyl peptidase‐4 inhibitors (DPP4i) in a real‐world setting. Methods: We conducted a matched cohort study using a prevalent new‐user design with time‐conditional propensity scores. New users of SGLT2i from seven Canadian provinces and the UK were matched to DPP4i users. The primary outcome was hospitalization with a diagnosis of urosepsis and the secondary outcome was Fournier's gangrene. Site‐specific hazard ratios for urosepsis comparing SGLT2i with DPP4i were estimated using Cox proportional hazards models and pooled using a random effects meta‐analysis. Results: We included 208 244 users of SGLT2i and 208 244 users of DPP4i. Among SGLT2i users, 42% initiated canagliflozin, 31% dapagliflozin and 27% empagliflozin. During a mean follow‐up of 0.9 years, patients initiating SGLT2i had a lower rate of urosepsis compared with those receiving DPP4i. The pooled adjusted hazard ratio was 0.58 (95% confidence interval [CI]: 0.42‐0.80). The incidence rates of Fournier's gangrene were numerically similar in SGLT2i (0.08 per 1000 person‐years; 95% CI: 0.05‐0.13) and DPP4i users (0.14; 95% CI: 0.09‐0.21). Conclusions: In this large, multi‐site study, we did not observe an increased risk for urosepsis associated with SGLT2i compared with DPP4i among patients with type 2 diabetes in a real‐world setting.